2017
DOI: 10.1159/000468975
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial Comparing Different Single Doses of Intravenous Paracetamol for Placement of Peripherally Inserted Central Catheters in Preterm Infants

Abstract: Background: The availability of a safe and effective pharmacological therapy to reduce procedural pain in preterm infants is limited. The effective analgesic single dose of intravenous paracetamol in preterm infants is unknown. Comparative studies on efficacy of different paracetamol doses in preterm infants are lacking. Objectives: To determine the analgesic effects of different single intravenous paracetamol doses on pain from peripherally inserted central catheter (PICC) placement in preterm infants. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 33 publications
0
4
0
2
Order By: Relevance
“…The principle is to convert the intra-atrial ECG to the body surface ECG through an intracardiac connection converter and directly observe changes in the cardiac P-wave electrophysiology under ECG monitoring. [21][22][23][24] However, the study of the tip location with the intracavitary ECG method for lower extremity ECC placement is still in its infancy. The focus of this study was to explore the feasibility of this technology for use in lower extremity central venous catheterisation.…”
Section: Discussionmentioning
confidence: 99%
“…The principle is to convert the intra-atrial ECG to the body surface ECG through an intracardiac connection converter and directly observe changes in the cardiac P-wave electrophysiology under ECG monitoring. [21][22][23][24] However, the study of the tip location with the intracavitary ECG method for lower extremity ECC placement is still in its infancy. The focus of this study was to explore the feasibility of this technology for use in lower extremity central venous catheterisation.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to non-pharmacological interventions (sucrose and dextrose), paracetamol-related analgesia was less effective to these nonpharmacological interventions. Similarly, Roofthooft et al also concluded that intravenous paracetamol (10, 15, or 20 mg/kg) was not effective (PIPP score and Comfort-Neo) as an analgesic during PICC placement in 60 preterm (<32 weeks) neonates, irrespective of the dose administered (67). This is in line with similar findings on the absence of an analgesic effect of even high doses of paracetamol (40 mg/kg oral) on pain, fear, or distress as reported in a cohort of children with oncological diseases when they had to undergo a needle insertion into their subcutaneous implanted venous access (68).…”
Section: Paracetamol For Acute Procedural Analgesia In Neonatesmentioning
confidence: 98%
“…Ацетаминофен является жаропонижающим средством, а также слабым анальгетиком, использование которого возможно у новорожденных детей. В настоящее время отсутствуют убедительные доказательства эффективности препарата в монотерапии острой боли [40,41], однако есть данные, что в комбинации с наркотическими анальгетиками для лечения послеоперационной боли ацетаминофен обладает опиоидсберегающим эффектом [42,43]. Исследования эффективности ацетаминофена в лечении боли и стресса у детей на ИВЛ отсутствуют.…”
Section: медикаментозная терапия нестероидные противовоспалительные п...unclassified